Characteristics of A1Si7Mg0.3/X-GNPs composites manufactured via stir casting method - Salleh, Mohd Shukor; Wakhi Anuar, Nur Farah Bazilah; Yahaya, Saifudin Hafiz; Omar, Mohd Zaidi; Ali, Mohd Azamuddin; Subramonian, Sivarao (Penerbit Universiti, UTeM, 2022)
Significant progress in graphene research has diverted interest to an emerging class of aluminium-based metal matrix composites. AlSi7Mg0.3 matrix composites reinforced with graphene nanoplatelets (GNPs) were fabricated via the stir casting technique. GNPs in varying amounts (0, 0.3, 0.5, 1.0 wt.%) were incorporated into the AlSi7Mg0.3 alloy via a mechanical stirring technique. Optical microstructures further analyzed the developed composites to discuss the microstructure evolution of alloys and composites. The hardness test was conducted to determine the strength of developed composites and supported by differential scanning calorimetry and X-ray diffraction. The results reveal the dendritic microstructure was decreased in the composites after adding various amounts of GNPs. The Vickers hardness value is significantly increased compared to as-cast alloy and the maximum hardness value (85.55 HV) was obtained for the AlSi7Mg0.3/0.3 wt.% GNPs. The outcomes demonstrate that incorporating a sufficient amount of GNPs into the AlSi7Mg0.3 alloy improves the hardness of the composite